2017
DOI: 10.1002/chem.201703202
|View full text |Cite
|
Sign up to set email alerts
|

Different and Often Opposing Forces Drive the Encapsulation and Multiple Exterior Binding of Charged Guests to a M4L6 Supramolecular Vessel in Water

Abstract: The supramolecular assembly [Ga L ] acts as a nanoscale flask to mediate the reactivity of encapsulated reactive guests and also functions as a catalyst to carry out enzyme-like chemical transformations. The guest binding to the interior cavity and exterior of this host is difficult to untangle because multiple equilibria occur in solution, and only when refining simultaneously data obtained from different techniques, such as NMR, UV/Vis, and calorimetry, can the accurate solution thermodynamics of these host-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 60 publications
(141 reference statements)
2
27
0
1
Order By: Relevance
“…Using the τ IP data in Fig. 5b, we found that the ion-pair formation and decay rates of K 8 (Si 4 L 6 ) and K 12 (Ga 4 L 6 ) were quite similar within the uncertainty of the measurements, resulting in a relative association rate ( suggests the presence of contact ion pairs in solution for bulkier counterion chemistries, and we conclude that 2-contact ion pairs are likely present in this system due to the low solvation state and ionic conductivity of the K 12 (Ga 4 L 6 ) cage 12 . The single hydration shell calculated for the K 8 (Si 4 L 6 ) cages suggest a 1-solvent shared ion pair, while the relative K a values suggest a 2-solvent pair to best match the K a values from the formation and decay rates (Supplementary Tables 1, 2, and Supplementary Fig.…”
Section: -6supporting
confidence: 57%
See 2 more Smart Citations
“…Using the τ IP data in Fig. 5b, we found that the ion-pair formation and decay rates of K 8 (Si 4 L 6 ) and K 12 (Ga 4 L 6 ) were quite similar within the uncertainty of the measurements, resulting in a relative association rate ( suggests the presence of contact ion pairs in solution for bulkier counterion chemistries, and we conclude that 2-contact ion pairs are likely present in this system due to the low solvation state and ionic conductivity of the K 12 (Ga 4 L 6 ) cage 12 . The single hydration shell calculated for the K 8 (Si 4 L 6 ) cages suggest a 1-solvent shared ion pair, while the relative K a values suggest a 2-solvent pair to best match the K a values from the formation and decay rates (Supplementary Tables 1, 2, and Supplementary Fig.…”
Section: -6supporting
confidence: 57%
“…1c, d). Complementary work on K 12 (Ga 4 L 6 ) cages by use of a combination of NMR, UV/vis spectroscopy, and ITC has previously characterized the association of large ammonium guests and counterions to the cage exterior via contact ion pairs, as those techniques are unable to detect K + ion-pair interactions 12 . These findings agree with our Z IB and G σ data, which also suggest that the K 12 (Ga 4 L 6 ) forms contact ion pairs, albeit with potassium counterions rather than large, strongly bound ammonium ions.…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Work by Arena, Raymond and co-workers nicely illustrates the different, and often opposing forces that lead to guest encapsulation in combination with the possibility of exterior binding. [62] It also underlines the necessity of using ar ange of different analytical techniques in order to fully understand the binding process of charged guests in and around coordination cages,a nd thus obtain all relevant thermodynamic parameters for guest binding in aqueous solution. Arena, Raymond and co-workers employed acombination of NMR and UV/Vis spectroscopy as well as calorimetry to untangle the multiple binding equilibria that are established upon introduction of acationic guest molecule into asolution of the tetrahedral polyanionic M 4 L 6 -type cage 2, [46] derived from naphthalene-based catechol ligand 1 that coordinates to Ga III ions ( Figure 2A).…”
Section: Guest Bindingmentioning
confidence: 99%
“…Eine Arbeit von Arena et al. veranschaulicht die verschiedenen und oft gegensätzlichen Kräfte, die zu einer Gastverkapselung, in Kombination mit der Möglichkeit für eine äußere Bindung, führen . Sie unterstreicht zudem die Notwendigkeit, eine Reihe analytischer Methoden heranzuziehen, um den Vorgang der Bindung von geladenen Gästen in und an Koordinationskäfigen vollständig zu verstehen und damit alle relevanten thermodynamischen Parameter für die Gastbindung in wässriger Lösung zu erhalten.…”
Section: Synthetische Anordnungenunclassified